2015
DOI: 10.1177/1521025115579670
|View full text |Cite
|
Sign up to set email alerts
|

How Final Is Leaving College While in Academic Jeopardy? Examining the Utility of Differentiating College Leavers by Academic Standing

Abstract: Retention research rarely differentiates between students dismissed from an institution for poor academic performance versus students leaving by choice. As a proxy for studying academic dismissal, this study investigated differences between students leaving college in academic jeopardy after the first year (<2.00 grade point average) and those leaving in good standing. These two types of academic leavers differed sharply in their 6-year completion outcomes, with students leaving in good standing most likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Though first‐year grades are good predictors of completion at 2‐ and 4‐year institutions (Allen & Robbins, ; Kopp & Shaw, ), an expanded analysis might include longer‐term outcomes (if available) such as retention into the second year, cumulative GPA beyond the first year, and program completion. To validate the use of first‐year outcomes in this study, supplemental analyses used data from the National Student Clearinghouse to investigate 6‐year degree completion rates by major group and attainment of the ACT Composite score benchmark of 23 for predicting FYGPA (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though first‐year grades are good predictors of completion at 2‐ and 4‐year institutions (Allen & Robbins, ; Kopp & Shaw, ), an expanded analysis might include longer‐term outcomes (if available) such as retention into the second year, cumulative GPA beyond the first year, and program completion. To validate the use of first‐year outcomes in this study, supplemental analyses used data from the National Student Clearinghouse to investigate 6‐year degree completion rates by major group and attainment of the ACT Composite score benchmark of 23 for predicting FYGPA (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to outcomes, this study focused on first‐year grades because they are proximal to ACT scores, they are typically used to establish college readiness benchmarks, and first‐year outcomes are strongly related to likelihood of completing a degree at 2‐ and 4‐year institutions (Allen & Robbins, ; Kopp & Shaw, ). Actual job success may be an appropriate criterion for establishing career readiness standards, but course grades are readily available and reflect greater standardization than performance evaluations or other workplace outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…In these models, intercepts were allowed to vary randomly across institutions. Institution-level variables of admission selectivity and enrollment size were also included in the models, as retention rates have been shown to vary by these characteristics (Kopp & Shaw, 2016; Lohfink & Paulsen, 2005). Interaction terms with parental education were examined to answer the second question; they were included when statistically significant at the .01 level.…”
Section: Methodsmentioning
confidence: 99%
“…Given that research has consistently shown a strong positive relationship between students’ precollege academic readiness levels and their likelihood of persisting and completing a degree (Adelman, 2006; Kopp & Shaw, 2016; Schmitt et al., 2009), the gaps in college success rates by parental education are often partially attributed to FG students not entering the college environment as well prepared and equipped academically as their CG peers. For instance, proportionally fewer FG students take rigorous coursework in high school and earn Advanced Placement or International Baccalaureate credits (Cataldi et al., 2018), while more FG students take remedial coursework in college (Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation